Sustainment of a complex culturally competent care intervention for Hispanic living donor kidney transplantation: A longitudinal analysis of adaptations. Issue 1 (28th March 2022) - Gordon, Elisa J.; Uriarte, Jefferson J.; Anderson, Naomi; Smith, Justin Dean; Caicedo, Juan Carlos; Shumate, Michelle
Abstract: Introduction: Sustainment refers to continued intervention delivery over time, while continuing to produce intended outcomes, often with ongoing adaptations, which are purposeful changes to the design or delivery of an intervention to improve its fit or effectiveness. The Hispanic Kidney Transplant Program (HKTP), a complex, culturally competent intervention, was implemented in two transplant programs to reduce disparities in Hispanic/Latinx living donor kidney transplant rates. This study longitudinally examined the influence of adaptations on HKTP sustainment. Methods: Qualitative interviews, learning collaborative calls, and telephone meetings with physicians, administrators, and staff (n = 55) were conducted over three years of implementation to identify HKTP adaptations. The Framework for Reporting Adaptations and Modifications-Expanded was used to classify adaptation types and frequency, which were compared across sites over time. Results: Across sites, more adaptations were made in the first year (n = 47), then fell and plateaued in the two remaining years (n = 35). Adaptations at Site-A were consistent across years (2017: n = 18, 2018: n = 17, 2019: n = 14), while Site-B made considerably fewer adaptations after the first year (2017: n = 29, 2018: n = 18, 2019: n = 21). Both sites proportionally made mostly skipping (32%), adding (20%), tweaking (20%), and substituting (16%) adaptation types. Skipping- and substituting-type adaptations were made due to institutional structural characteristics and lack of available resources, respectively. However, Site-A's greater proportion of skipping-type adaptations was attributed to greater system complexity, and Site-B's greater proportion of adding-type adaptation was attributed to the egalitarian team-based culture. Conclusion: Our findings can help prepare implementers to expect certain context-specific adaptations and preemptively avoid those that hinder sustainment.